Beneficial and harmful effects of nonselective beta blockade on acute kidney injury in liver transplant candidates. Issue 6 (26th May 2017) - Kim, Sang Gyune; Larson, Joseph J.; Lee, Ji Sung; Therneau, Terry M.; Kim, W. Ray
Abstract : Nonselective beta‐blockers (NSBBs) have played an important role in the prevention of portal hypertensive bleeding in patients with cirrhosis. However, recent studies have suggested that NSBBs may be harmful in some patients with end‐stage liver disease. The purpose of this article is to evaluate the association between use of NSBB and the incidence of acute kidney injury (AKI). We conducted a nested case‐control study in a cohort of liver transplant wait‐list registrants. Each patient with AKI was matched to a control by the Model for End‐Stage Liver Disease–Na score, age, serum creatinine, and follow‐up duration. Out of a total of 2361 wait‐list registrants, 205 patients developed AKI after a median follow‐up duration of 18.2 months. When compared with matched controls, ascites (79.0% versus 51.7%) and non‐Caucasian race (16.6% versus 7.8%) were more common among the cases. The frequency of NSBB use was higher among the cases than controls, albeit insignificantly (45.9% versus 37.1%; P = 0.08). In multivariate analyses, the impact of nonselective beta blockade on the development of AKI was dependent on the presence of ascites: nonselective beta blockade in patients with ascites significantly increased the risk of AKI (hazard ratio [HR], 3.31; 95% confidence interval [CI], 1.57‐6.95), whereas in patients without ascites, NSBB use reduced it (HR, 0.19; 95% CI, 0.06‐0.60). Potential benefits and harms of a NSBB in terms of AKI depend on the presence of ascites in liver transplant candidates. NSBB therapy in patients with cirrhosis may need to be individualized. Liver Transplantation 23 733–740 2017 AASLD .